Comprehensive analysis and experiments identified ANXA1 as an unfavorable prognosticator in glioma - Yu Fan; Yanwen Chen; Xingda Run; Huaide Qiu; Qianxing Hu; Xudong Zhao; ZhongYuan Bao; Zengli Miao (Translational Oncology)
Background: ANXA1 was upregulated in gliomas in previous bulk sequencing studies. we examined the role of ANXA1 in glioma using bioinformatics analysis and experiments. Methods: Two cohorts were adopted to validate the prognostic value of ANXA1 in gliomas. Real-time quantitative PCR and western blotting were performed on samples for further validation. Using the data of GSE162631, ANXA1 expression was analyzed in different cells in glioblastoma specimen. In different groups, lentiviral vector or the empty vector was used to construct cell lines. Wound-healing assay, along with Transwell assay, was conducted to assess the migration and invasion of glioma cells. Animal studies were conducted to examine the role of ANXA1 in gliomas. Results: ANXA1 expression was associated with overall survival in glioma patients. In glioblastomas, ANXA1 expression was higher than in low-grade gliomas. Among patients receiving chemo- or radiotherapy, high ANXA1 expression presented a shorter overall survival. Single-cell sequencing showed that ANXA1 was expressed in a higher proportion and level in glioblastomas cells than in normal cells; whereas, ANXA1 was enriched in T cells among immune cells. As shown in experiments, knockdown of ANXA1 could attenuate the proliferation, migration and invasion of glioma cells in vitro and vivo, thereby improving the prognosis of animals. Conclusions: ANXA1 can promote the proliferation, migration and invasion of glioma; its expression is positively correlated with immune response and poor prognosis of glioma. The cancer-promoting mechanisms of ANXA1 in glioma and its correlation with the functional status of glioma patients warrant further investigation.